Intermediate microeconomics : price theory and applications - Ekelund, Robert B. 1940- (D.C. Heath, 1995)
Introduction to microeconomic theory. Theory of consumer behavior. The theory of the firm. Market structures. Resource markets. The role of government in markets and international trade.